The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31227/osf.io/d37k4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Evaluation on the Instructions in the English Textbook for 10th Grade Students Entilted Bahasa Inggris Published by Ministry of Education and Culture of Indonesia

Abstract: This research is an evaluative research conducted to find out the quality of TheEnglish Textbook for 10th Grade Students entitled “Bahasa Inggris” by the IndonesianMinistry of Education and Culture in terms of instruction used. The instrument ofthis research was an evaluation format used by the researcher as the guidelines toevaluate the textbook. The evaluation format contained instruction categoriesthat consists of three indicators as the criteria of good instructions. After theevaluation, it was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In Harmer (1998), they rely on presentation, practice, and production (Littlejohn 1998:205). According to Sari et al, (2018), the objectives and activities in the two textbooks he reviewed did not match the requirements for an excellent textbook and needed to be modified. Furthermore, the order in which the texts in the book were presented in the book required some changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Harmer (1998), they rely on presentation, practice, and production (Littlejohn 1998:205). According to Sari et al, (2018), the objectives and activities in the two textbooks he reviewed did not match the requirements for an excellent textbook and needed to be modified. Furthermore, the order in which the texts in the book were presented in the book required some changes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, some studies have reviewed the significant relationship between integrating critical discourse analysis and textbooks. Research conducted by Sari et al, (2018) in the journal entitled "An analysis of the activities in the Bahasa Inggris textbook for 10th grade students published by the Indonesia Ministry of Education and Culture" revealed that this English textbook is an excellent textbook since it only contains one category, which is uncommon in this textbook: pushing pupils to make grammatical discoveries from a basic exercise. The other requirements were as numerous as the activities supplied by this book.…”
Section: Introductionmentioning
confidence: 99%
“…Some English textbook investigations had been conducted in terms of instructions, tasks, and activities. However, one of the research found that the English textbook instruction was not good enough for students since it did not help them to build their critical thinking (Maharani et. al, 2018).…”
Section: Introductionmentioning
confidence: 99%